TINJAUAN EFEKETIFITAS PERENCANAAN DALAM PENGELOLAAN DANA DESA DI DESA TUMBANG JUTUH, KECAMATAN RUNGAN, KABUPATEN GUNUNG MAS - Nina Dwicahyani; Jovano Deivid Oleyver Palenewen (Jurusan Ilmu Pemerintahan, 2021)
In this study, the researcher used the Minister of Home Affairs Regulation Number 113 of 2014 concerning Village Financial Management Article 2 Paragraph 1 which states that : village finance must be managed based on the principles of being transparent, accountable, participatory, as well as orderly and budgetary discipline, as a reference in preparing research result. The research method used is descriptive qualitative method. With data collection techniques namely observation, interviews, and documentation. Data analysis techniques are qualitative and quantitative approaches. Qualitative approach includes : data reduction, data presentation, and drawing conclusions. The quantitative approach includes analysis result from village fund management planning documents.The results of this study indicate that the effectiveness of village fund management planning in Tumbang Jutuh Village has been implemented effectively. This is evidenced by the implementation of principles of transparency, accountability, participatory, orderly and budgetary discipline in planning, namely by the existence of village development planning meetings involving village communities, preparation of APBDes, RKP, RPJMDes and village development realization reports that are adjusted to village priorities and guided by regulations applicable